Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) sebagai Upaya Menciptakan Lingkungan Bersih dan Bebas dari Penyakit di SDN 007 Sungai Pinang Kota Samarinda - Nur, Azizah; Destyra H, Aulia; Khisanta P, Pryenalvend; Narsa, Angga Cipta (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Clean and Healthy Living Behavior (PHBS) is an important concept in creating a healthy and productive generation. Healthy habits implemented from an early age will have a positive impact on health, especially for children. In elementary school, children begin to learn about personal hygiene, the importance of a nutritious diet, and environmental cleanliness. The impact of a lack of understanding of PHBS in elementary school children that often appears is diarrhea. Through health promotion activities regarding PHBS in schools as an education for children to understand the importance of PHBS. The PHBS implementation method is: (1) interactive education through presentations and leaflets, (2) hand washing demonstrations, and (3) pre-tests and post-tests to evaluate understanding. The results of the Pre-test and Post-test were analyzed descriptively quantitatively with Microsoft Excel and calculated the value of each student, the class average, each question will be analyzed using SPSS by conducting a normality test and continued with a non-parametric Wilcoxon Signed Rank Test.